2019
DOI: 10.1136/bmjopen-2018-027748
|View full text |Cite
|
Sign up to set email alerts
|

Association between infection withHelicobacter pyloriand platelet indices among school-aged children in central Ethiopia: a cross-sectional study

Abstract: ObjectivePrevious clinical studies in adults from developed countries have implicated Helicobacter pylori infections in the development of thrombocytopenia. However, studies in children, particularly those from low-income countries, are unusually scarce. We examined the association between H. pylori infection and platelet indices in young Ethiopian school children.DesignCross-sectional studySettingThis study was conducted in five elementary schools located in central Ethiopia.ParticipantsBlood and stool sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(27 reference statements)
0
5
1
Order By: Relevance
“…RUT combined with histology [86] and culture [106] has also been used in the diagnosis of HPI in Cameroon. In Ethiopia, an East African country, reports on the diagnosis of HPI are largely based on serology and SAT [87,88,[107][108][109]. On the other hand, Kenya, a neighboring country, has reports on the use of SAT [89,90], endoscopy, RUT, histol-ogy, and culture [91,110].…”
Section: Non-invasive Invasivementioning
confidence: 99%
“…RUT combined with histology [86] and culture [106] has also been used in the diagnosis of HPI in Cameroon. In Ethiopia, an East African country, reports on the diagnosis of HPI are largely based on serology and SAT [87,88,[107][108][109]. On the other hand, Kenya, a neighboring country, has reports on the use of SAT [89,90], endoscopy, RUT, histol-ogy, and culture [91,110].…”
Section: Non-invasive Invasivementioning
confidence: 99%
“…who found that a significant difference was found between various WBC quartiles for H pylori infection (P = 0.001).This may be explained by our study was cross sectional study in contrary to their cohort study which enabled them to follow the children properly. Also Baxendell et al [34]. found that H. pylori-infected children had lower red blood cell counts (p=0.005) compared with non-infected .also found that an association between H. pylori infections and reduced platelet indices in young Ethiopian school children.…”
Section: Resultsmentioning
confidence: 89%
“…33 A second reported that the benefit of MPV as an inflammatory marker to determine the disease activity in TB patients 34 and a third noted a higher MPV in children infected with Helicobacter pylori infection than in healthy controls. 35 Overall, it is thought that during an acute infection such as septicemia the initial increase in MPV level can be related to thrombocytopenia and during chronic or persisted bacterial infection a delayed decline in MPV level can be related to thrombocytosis. 36 Here, we should report some limitations of this study.…”
Section: Discussionmentioning
confidence: 99%